Analisis Perbandingan Fluid Viscous Damper dan Fixed Base Terhadap Beban Siklik dengan Finite Element: Comparative Analysis of Fluid Viscous Damper and Fixed Base Against Cyclic Loads with Finite Element - Azhar, Muhammad Farrel; Arini, Resti Nur; Kurnia, Fadli (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2023)
The geographical location of Indonesia, which is very at risk of earthquake disasters, requires the planning of building structures that are resistant to earthquake risks, one of which is by using base isolators. A base isolator system can improve structural performance by dissipating earthquake energy with its flexibility character to increase the vibration period. One type of base isolator is the Fluid Viscous Damper (FVD), which can be applied to high-rise buildings that often experience destruction during earthquakes. This research aims to determine the energy dissipation and ductility of fixed base structures and structures using FVD with finite element method using ABAQUS application. The object of analysis of this study uses a two-story portal with a steel structure. The results of this study obtained the characteristics of the two building models are semi-ductile, but there are differences in the ductility value between the two models. Based on the calculation results, the deviation ductility value that occurs in the fixed base building model is 2.624. Meanwhile, the deviation ductility of the FVD building model is 4.104. The use of FVD can increase the ductility value by 22%. The dissipation that can be done by the fixed base building model is 0.119, and the energy dissipation value for the building model with FVD is 0.156. Using FVD can increase energy dissipation in the analyzed model by 13.45%.